The Influence of Child Maltreatment on Young Adult Attachment Style in the Novel Needlework by Deirdre Sullivan - Dina Regita Putri; Adi Prautomo (Faculty of Letters Universitas Balikpapan, 2023)
This thesis studies the types of child maltreatment and its influence on young adult attachment style in the novel Needlework by Deirdre Sullivan. The aims of this research are: 1) To find out the types of child maltreatment in the novel Needlework by Deirdre Sullivan, and 2) To describe the child maltreatment that influences young adult attachment style in the novel Needlework by Deirdre Sullivan. The theory used in this research is Perrin’s child maltreatment theory and Bartholomew’s attachment theory. This research used qualitative methodology research, which is presented descriptively. The researcher collected the data from the excerpt related to the theory in the novel Needlework, written by Deirdre Sullivan and published in 2016. The final result of this research is the researcher found 74 data of child maltreatment influencing young adult attachment style with the most dominant data of child maltreatment is neglect with 40% of the data (30 out of 74 data) which is influencing the young adult attachment style of the character into fearful-avoidant as much as 50% data (15 out of 30 data).